Mitochondrial Quality Control in the Maintenance of Cardiovascular Homeostasis: The Roles and Interregulation of UPS, Mitochondrial Dynamics and Mitophagy - Yujie Song (Hindawi Limited, 2021)
Maintenance of normal function of mitochondria is vital to the fate and health of cardiomyocytes. Mitochondrial quality control (MQC) mechanisms are essential in governing mitochondrial integrity and function. The ubiquitin-proteasome system (UPS), mitochondrial dynamics, and mitophagy are three major components of MQC. With the progress of research, our understanding of MQC mechanisms continues to deepen. Gradually, we realize that the three MQC mechanisms are not independent of each other. To the contrary, there are crosstalk among the mechanisms, which can make them interact with each other and cooperate well, forming a triangle interplay. Briefly, the UPS system can regulate the level of mitochondrial dynamic proteins and mitophagy receptors. In the process of Parkin-dependent mitophagy, the UPS is also widely activated, performing critical roles. Mitochondrial dynamics have a profound influence on mitophagy. In this review, we provide new processes of the three major MQC mechanisms in the background of cardiomyocytes and delve into the relationship between them.